Adult ileocecal intussusception induced by adenomatous ileal polyp: case report and literature review - Gueye, M L (J Surg Case Rep, 2018)
Intussusception is a rare cause of bowel obstruction in adults, and has generally an organic etiology. However, adenomatous polyp of the small bowel is an uncommon etiology. Moreover, there’s a great difference with childhood intussusception in its presentation, etiology and management. We describe herein a case of adult ileocecal intussusception due to an adenomatous ileal polyp with a preoperative diagnosis made on computed tomography. We performed a right hemicolectomy, without attempting to reduce the intussusception, and an end-to-end ileotransverse anastomosis. The pathological examination of the surgical specimen revealed an adenomatous polyp with a high grade dysplasia on the terminal ileum, being the cause of the ileocecal intussusception.